2017
DOI: 10.1161/circoutcomes.116.003863
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Mortality in the WISE Study (Women’s Ischemia Syndrome Evaluation)

Abstract: Background The Women’s Ischemia Syndrome Evaluation (WISE) was a prospective cohort study of 936 clinically stable symptomatic women who underwent coronary angiography to evaluate symptoms and signs of ischemia. Long-term mortality data for such women are limited. Methods and Results Obstructive coronary artery disease (CAD) was defined as ≥50% stenosis on angiography by core lab. We conducted a National Death Index search to assess the mortality of women who were alive at their final WISE contact date. Deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 40 publications
(31 reference statements)
1
63
0
2
Order By: Relevance
“…Longer‐term follow‐up data from the WISE project confirmed a worse prognosis than previously thought for stable INOCA women where 10‐year all‐cause death and cardiac death rates were 17% and 11%, respectively, in women with nonobstructive CAD, and 10% and 6%, respectively, in women with normal coronary arteries 40. Furthermore, a recent meta‐analysis of 48 studies including patients presenting with stable symptoms undergoing either invasive or noninvasive coronary angiography demonstrated odds ratios of 1.57 to 1.7 for MACE defined as cardiac death, nonfatal MI, hospitalization for unstable angina, or revascularization in patients with NOCAD compared with their counterparts with normal coronary arteries.…”
Section: Evidence Of An Adverse Prognosismentioning
confidence: 54%
See 2 more Smart Citations
“…Longer‐term follow‐up data from the WISE project confirmed a worse prognosis than previously thought for stable INOCA women where 10‐year all‐cause death and cardiac death rates were 17% and 11%, respectively, in women with nonobstructive CAD, and 10% and 6%, respectively, in women with normal coronary arteries 40. Furthermore, a recent meta‐analysis of 48 studies including patients presenting with stable symptoms undergoing either invasive or noninvasive coronary angiography demonstrated odds ratios of 1.57 to 1.7 for MACE defined as cardiac death, nonfatal MI, hospitalization for unstable angina, or revascularization in patients with NOCAD compared with their counterparts with normal coronary arteries.…”
Section: Evidence Of An Adverse Prognosismentioning
confidence: 54%
“…Documented MACE rates in stable INOCA patients are summarized in Table 1 4, 10, 15, 26, 35, 36, 37, 38, 39, 40, 41. Additionally, many of these patients have an adverse quality of life, functional status, and exercise capacity with relatively frequent visits to healthcare providers for persistent or recurring disabling symptoms 42.…”
Section: Evidence Of An Adverse Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The 10‐year follow‐up from the WISE study demonstrated a 20% mortality rate in women referred for invasive angiography for symptoms of ischemia. In those who did not have obstructive disease, the 10‐year mortality was 13%, significantly greater than asymptomatic age‐matched controls (2.8%) …”
Section: Cardiomyopathiesmentioning
confidence: 84%
“…However, despite the lack of obstructive CAD, women who present with symptoms of angina have a higher mortality than asymptomatic females. The WISE (Women's Ischemic Syndrome Evaluation) study demonstrated that women experience symptoms of obstructive CAD differently than men, with older women more likely to present in a typical pattern . During their event, women may present with symptoms of shortness of breath (58%), weakness (55%), unusual fatigue (43%), diaphoresis (39%), and dizziness (39%) .…”
Section: Cardiomyopathiesmentioning
confidence: 99%